The "silent art" of ancient China : historical analysis of the intellectual and philosophical influences in the earliest medical corpus LING SHU CHING - Lee, Francis R., 1931-; Saunders, John Bertrand de Cusance Morant, 1903-1991 (Tapei : Linking Publishing Co. Ltd., 1985)
De "silent art" waarvan sprake in de titel is de traditionele geneeskunde zoals deze nog altijd in praktijk gebracht wordt in China.